Using science as a differentiator in a crowded digital mental health market - Jennifer Huberty; Clare C. Beatty; Jacqlyn Yourell (Frontiers Media S.A., 2024)
The digital mental health industry has seen remarkable growth in recent years. However, within this crowded landscape, many companies overlook a critical factor for gaining a competitive edge: the integration of science. In this context, "science" refers to the strategic collection and analysis of information (i.e., data) at digital mental health companies, aimed at guiding business decisions and achieving business objectives. This paper demonstrates that science is integral, yet underutilized in the digital mental health industry, with common misconceptions about its role. When science is integrated within a company, it enables them to (1) innovate, (2) understand customers, (3) make informed decisions, and (4) drive revenue. Digital mental health companies recognizing the multifaceted value of science may be better equipped for sustainable growth and success amid the crowded digital health market.